Landskabet som metafor hos Henrik Pontoppidan - de Thurah, Christian (Pontoppidaniana, 2025)
Abstract It is well-known that landscapes play an important role in Henrik Pontoppidan´s works. But the landscapes are not only used by the author to create a backdrop for the plot, they are also part of a metaphorical deep structure in the texts. In this essay, Christian de Thurah examines one of Pontoppidan´s minor novels, Højsang, in order to show in detail how Pontoppidan made use of this metaphorical layer.